2021
DOI: 10.1200/po.20.00540
|View full text |Cite
|
Sign up to set email alerts
|

Budget Impact Analysis of Comprehensive Genomic Profiling in Patients With Advanced Non–Small-Cell Lung Cancer

Abstract: PURPOSE This study assessed the economic impact of increased use of comprehensive genomic profiling (CGP) versus conventional testing strategies among patients with advanced non–small-cell lung cancer (aNSCLC) from a US commercial health plan perspective. METHODS A decision analytic model was developed to estimate the incremental benefits and costs across testing methodologies (CGP v non-CGP), as well as across sample types (tissue-based and liquid-based), for patients with newly diagnosed aNSCLC. Model outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…b Refs. 38 , 39 , 62 - 65 . NGS, next-generation sequencing; OS, overall survival; PFS, progression-free survival.…”
Section: Resultsmentioning
confidence: 99%
“…b Refs. 38 , 39 , 62 - 65 . NGS, next-generation sequencing; OS, overall survival; PFS, progression-free survival.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have evaluated the cost of NGS panel testing by the use of budget impact models including multiple assumptions that may limit the external applicability of the results to real-world contexts. 22 For example, some prior studies have included the assumption that patients have wide access to all the potential matched therapies available or lack real-world efficacy outcomes and instead use survival times obtained on clinical trial reported data. 22 The use of estimates based on clinical trial data may overestimate the benefit provided by NGS panel testing.…”
Section: Discussionmentioning
confidence: 99%
“… 22 For example, some prior studies have included the assumption that patients have wide access to all the potential matched therapies available or lack real-world efficacy outcomes and instead use survival times obtained on clinical trial reported data. 22 The use of estimates based on clinical trial data may overestimate the benefit provided by NGS panel testing.…”
Section: Discussionmentioning
confidence: 99%
“…The model also included other monthly medical service costs reflecting outpatient visits, interventions, and unplanned hospitalizations unrelated to AEs from a previous publication for the United States ( 19 ). These costs were converted to local costs in the remaining countries using differences in PPP.…”
Section: Methodsmentioning
confidence: 99%